Prediction of preterm premature membrane rupture by the platelet-lymphocyte ratio - Sultana, Nargis; Karim, Farha; Rahman, Mohammad Khalilur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Premature rupture of membranes is a significant obstetric problem. Evaluating platelet -lymphocyte ratio is expected to illuminate the potential scope of early prediction of PPROM. This study showed that PLR could be a new inflammatory marker for diagnosing preterm PROM. Methods: The study place was the Department of Obstetrics and Gynaecology, Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh, from May 2019 to October 2019. Results: It was a case-control study. All mothers were selected by purposive sampling who were PPROM as cases. Age-matched non-PPROM pregnant women at term were also enrolled as control. Afterward, they were scrutinized according to eligibility criteria, and 200 mothers were enrolled. Among them, 100 were cases, and the other 100 were in control. A pre-tested, observation-based, peer-reviewed data collection sheet was prepared before the study. Data regarding clinical, biochemical, and surgical profiles were recorded. Data were compiled, edited, and analyzed. The P-value was determined by the chi-square test (categorical variables) and the student’s t-test (continuous variables). The p-value was significant at <0.05. Conclusions: The mean age of 100 patients from the case was 24.39±2.81 (age range: 18-36) years, and that of the control, like 100 normal pregnant women, was 24.31±2.34 (age range: 19-35) (p=0.49). The mean parity of case and control were 2.1±0.9 (range: 0-5) and 1.98±0.2 (range: 0-3). The mean gravida of case and control were (3.1±1.2 vs. 3.4±1.4). Platelet count was found to be significantly higher in preterm PROM group (case) than control (241.6±58.7×1000/mm³ vs. 201.7±65.9 ×1000/mm³), p value is <0.001 which is statistically significant. So, PLR might be an excellent inflammatory biomarker to predict preterm PROM.